2016
DOI: 10.1287/orsc.2016.1076
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Structure and Performance Feedback: Centralization, Aspirations, and Termination Decisions

Abstract: T his study examines the effects of organizational structure and performance feedback on termination decisions-in particular, product phaseout. Using quarterly product-level data on the major mobile handset manufacturers for the period 2004-2009, we analyze how product-level feedback affects product phaseout and how these decisions are conditioned by organizational structure-the extent to which decision making is centralized. We argue that such structure affects termination in two ways: directly, through coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 104 publications
4
106
0
2
Order By: Relevance
“…This, in turn, addresses another issue that performance feedback theory faces: it predicts that firms make changes when performance is below aspirations, but it does not predict what those changes will be. Prior work has linked performance feedback to a wide range of dependent variables, such as research and development (R&D) expenditure (Greve, 2003b), market position (Greve, 1998a), product portfolio decisions (Gaba and Joseph, 2013;Joseph, Klingebiel, and Wilson, 2016), and technology sourcing strategy (Gaba and Bhattacharya, 2012;Lungeanu, Stern, and Zajac, 2016;Eggers and Kaul, 2018). When multiple things could be changed, however, it is not clear which one managers will focus on (Greve, 2018).…”
Section: Contributions To Research On Performance Feedbackmentioning
confidence: 99%
“…This, in turn, addresses another issue that performance feedback theory faces: it predicts that firms make changes when performance is below aspirations, but it does not predict what those changes will be. Prior work has linked performance feedback to a wide range of dependent variables, such as research and development (R&D) expenditure (Greve, 2003b), market position (Greve, 1998a), product portfolio decisions (Gaba and Joseph, 2013;Joseph, Klingebiel, and Wilson, 2016), and technology sourcing strategy (Gaba and Bhattacharya, 2012;Lungeanu, Stern, and Zajac, 2016;Eggers and Kaul, 2018). When multiple things could be changed, however, it is not clear which one managers will focus on (Greve, 2018).…”
Section: Contributions To Research On Performance Feedbackmentioning
confidence: 99%
“…Although changing firm behavior as a response to PRA represents a general phenomenon (Bromiley, ; March, ), firms differ in how they interpret and react to this information. Firm responses to PRA vary with firm governance arrangements, resources, and organizational structures (Desai, ; Joseph, Klingebiel, & Wilson, ; Kuusela, Keil, & Maula, ). Indeed, previous research has shown that a firm's entrepreneurial (Hoskisson, Chirico, Zyung, & Gambeta, ; Naldi, Nordqvist, Sjöberg, & Wiklund, ), strategic (Audia, Locke, & Smith, ; Vissa, Greve, & Chen, ), or temporal (Bromiley & Souder, ) orientation can influence its response to PRA.…”
Section: Introductionmentioning
confidence: 99%
“…Along similar lines, the effects of centralizing versus decentralizing tactical decision making—as regards, for instance, product or technology choices—have been explored in the telecommunications industry. For example, (Joseph, Klingebiel, & Wilson, ) discussed how, because of different problem‐solving processes, the locus of decision making affects the content of a firm's key strategic decisions.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Along similar lines, the effects of centralizing versus decentralizing tactical decision making-as regards, for instance, product or technology choices-have been explored in the telecommunications industry. For example, (Joseph, Klingebiel, & Wilson, 2016) discussed how, because of different 1 Over the past several decades, scholars have explored the drivers of reorganization in some detail. The causes most often studied are selection pressures exerted by changes in a firm's scope and/or external environment (Burns & Stalker, 1961;Chandler, 1962;Davis et al, 2009;Girod & Whittington, 2017;Hannan & Freeman, 1984;Karim, Carroll, & Long, 2016) and the desire to innovate or to improve efficiency through repeated reorganizations (Karim, 2006(Karim, , 2009(Karim, , 2012Karim & Kaul, 2015).…”
Section: Structure As An Internal Driver Of Reorganizationsmentioning
confidence: 99%